Efeitos do uso de palmilhas com cunha medial na biomecânica da corrida no plano sagital - Michelle Sena de Castro Silva (2022)
Running is a complex activity that involves several joints, three planes of motion, and has become increasingly popular worldwide. Running, however, is associated with a high prevalence of musculoskeletal injuries. Different biomechanical factors seem to be associated with the occurrence of injuries in runners, including excessive foot pronation. Medially wedged insoles at the forefoot and hindfoot are described in the literature as an intervention to reduce excessive foot pronation and associated knee and hip movements during the stance phase of running. However, the effects of using this type of insole on lower limb biomechanics in the sagittal plane during running are still unclear. Thus, this dissertation aimed to investigate the effect of a medially wedged insole at the forefoot, hindfoot, and arch support on the ankle, knee, and hip kinematics and kinetics during the stance phase of running in the sagittal plane. Nineteen recreational runners who had rearfoot strike patterns and excessive pronation were evaluated. Shank-forefoot alignment, leg length, and dorsiflexion range of motion were measured. Reflective markers were placed on anatomical landmarks of the pelvis and lower limbs. Eight infrared cameras (Qualysis, Sweden) and three force platforms were used to collect angular variables and moments of force of the hip, knee, and ankle during the stance phase of running in two conditions: i) control condition: semi-rigid arch support insole and flat at the forefoot and hindfoot and ii) insole condition: semi-rigid arch support insole with 7-degree medial wedge at forefoot and hindfoot. Data were processed using Visual3D software. After checking normality with Shapiro-Wilk test, dependent samples t-test was used to compare the two conditions. Significance was set at p-value < 0.05. Data were analyzed using SPSS. The insole condition increased peak ankle dorsiflexion during the stance phase of running. However, no differences were found in the angular displacement of the knee and hip and moments of force of the ankle, knee, and hip in the sagittal plane. Therefore, insoles with 7-degree medial wedge at the forefoot and hindfoot change ankle kinematics during the stance phase of running, with no effect on knee and hip kinematics and kinetics.